ঢাকার স্মৃতি ৮ - মামুন, মুনতাসীর 1951-; Stock, A. G. (Amy Geraldine), 1902-1988 (Māolā Brādārsa, মাওলা ব্রাদার্স, 2001)
Collection of autobiographical reminiscences of 18th-19th and early 20th century social history of Dhaka, Bangladesh, written by various Bengali writers.